El estrés y su influencia en el desempeño laboral de los trabajadores de la Municipalidad Distrital de Curgos - Provincia de Sánchez Carrión 2016 - Carranza Araujo, Alfonsina Oligoria (2019)
The present research work has been carried out in the district municipality of Curgos province of Sánchez Carrión, Department of Libertad, in Peru. Having as main objective "to establish how stress influences the labor performance of the workers of the district municipality of Curgos, province of Sánchez Carrión". The research problem was: How does stress influence the work performance of the employees of the District municipality of Curgos, province of Sánchez Carrión 2016? In the research, the non-experimental design was applied. The population was conformed by 40 servants of the District Municipality of Curgos; the sample being the 40 servers for being small, and to whom the survey could be applied; According to the results obtained, it has been possible to qualify the variables under study, then the analysis and discussion has been carried out, even demonstrating the validity of the hypothesis that: "Stress has a negative influence on the job performance of workers of the District Municipality of Curgos, province of Sánchez Carrión, 2016 ". Finally, the conclusions and recommendations have been formulated. The main conclusion establishes according to Pearson's correlation coefficient, the influence relation is r = -0.856 which means that there is a negative influence relationship, besides both "stress" and "work performance" have obtained ratings that in most of them are located on a "medium" level; This indicates that greater stress less performance, and less stress, higher performance. So it is recommended that to improve stress, the most important thing is to identify the most influential stressors that afflict the worker, which prevents him from performing his functions well, in order to know the cause of his performance being affected, for this It is necessary to apply a test based on questions related to your work or through an interview, which allows you to identify and link the stressors with the low performance of the workers.